The Role of National Narcotics Regency in the Drug Abuse Prevention Program in Mempawah Regency - Chainar, Chainar; Purnama, Desca Thea; Marini, Marini; Rasidar, Rasidar; Darmawan, Deni (LifeSciFi, 2024)
Drug abuse is a serious problem that threatens the younger generation, including teenagers, in Mempawah Regency. The District National Narcotics Agency (Badan Narkotika Nasional Kabupaten/Kota or BNNK) has an essential role in the prevention and eradication of drug abuse and illicit circulation (P4GN) program. This study aims to describe the role of BNNK in the P4GN program in Mempawah Regency. This study uses a qualitative method with descriptive analysis, a technique for determining purposive sampling informants according to the criteria; the informants in this study consist of representatives of adolescents, the government, schools and BNNK officers. Data collection techniques include observation, interviews, documentation, and data validation techniques using triangulation. The results of the research show that BNNK Mempawah has carried out and carried out its role as the implementing officer of the P4GN program, among its roles in conducting education and counseling about the dangers of drugs, early detection through random urine tests and rehabilitation as well as strict law enforcement. The researcher also gave several recommendations so that the role of BNNK is more optimal, and the recommendations are to increase Penta helix cooperation between agencies (government, private sector, academics, community and media), increase budget and human resource development, utilize technology and anti-stigma campaigns.